Update in Viral Infections in the Intensive Care Unit - Fragkou, Paraskevi C.; Moschopoulos, Charalampos D.; Karofylakis, Emmanouil; Kelesidis, Theodoros; Tsiodras, Sotirios (Frontiers in Medicine, 2021)
The advent of highly sensitive molecular diagnostic techniques has improved our ability to detect viral pathogens leading to severe and often fatal infections that require admission to the Intensive Care Unit (ICU). Viral infections in the ICU have pleomorphic clinical presentations including pneumonia, acute respiratory distress syndrome, respiratory failure, central or peripheral nervous system manifestations, and viral-induced shock. Besides de novo infections, certain viruses fall into latency and can be reactivated in both immunosuppressed and immunocompetent critically ill patients. Depending on the viral strain, transmission occurs either directly through contact with infectious materials and large droplets, or indirectly through suspended air particles (airborne transmission of droplet nuclei). Many viruses can efficiently spread within hospital environment leading to in-hospital outbreaks, sometimes with high rates of mortality and morbidity, thus infection control measures are of paramount importance. Despite the advances in detecting viral pathogens, limited progress has been made in antiviral treatments, contributing to unexpectedly high rates of unfavorable outcomes. Herein, we review the most updated data on epidemiology, common clinical features, diagnosis, pathogenesis, treatment and prevention of severe community- and hospital-acquired viral infections in the ICU settings.